How to increase efficiency with the certification of process compliance - Gallina, Barbara (My University, 2017)
Certification as well as self-assessment of safety-critical systems is an expensive and time-consuming activity due to the necessity of providing numerous deliverables. These deliverables can be process-related or product-related. Process-related deliverables are aimed at showing compliance with normative documents (e.g., safety standards), which impose specific requirements on the development process (e.g., reference models for the safety life-cycles). In this lecture, we limit our attention to process-related deliverables and we propose a solution aimed at reducing time and cost related to their provision. Our solution consists of the combination of three approaches: the safety-oriented process line engineering approach, the process-based argumentation line approach, and the model driven certification-oriented approach. More specifically, we define how these three approaches are combined and which techniques, tools and guidelines should be used to implement the resulting approach. Then, via small-sized but realistic process-fragments, we illustrate it. Finally, we present a roadmap for future research directions.
Keywords: Bases de datos - Medidas de seguridad; Safety-critical systems; Certification; Self-assessment